Meso e macrofauna de solo cultivado com milho e irrigado com água residuária da suinocultura - Castaldelli, Ana Paula Almeida (2013)
The use of soil fauna as anthropogenic and environmental changes tillage systems has been growing in recent years. However, still there are few long-term studies that relate these organisms with application of organic residues in the soil. This study aimed to evaluate, in two cycles of culture of maize, the effects of the application of different doses and types of swine wastewater (ARS) combined or not with mineral fertilization on the edaphic meso and macrofauna. Four doses (0, 100, 200, 300 m3 ha-1) of ARS, treated in anaerobic digester in the first year of study and raw waste in the second year, associated or not with mineral fertilization were applied in two cycles of culture of maize totaling 24 experimental plots, being 12 using mineral fertilizer. Pit-fall traps were installed in each of the plots to be sampled soil fauna and the results were evaluated by multivariate statistical techniques (NMS and Per-MANOVA). The application of ARS both raw waste as treated in anaerobic digester and mineral fertilizacion did not influence soil fauna. Chemical soil parameters differed the edaphic meso and macrofauna only between the years